Potassium induced metabolic changes with or without NaCl salinity in maize plants growing in aridlands - Mouza S. M. Ali; Shyam Kurup; Mohammed A. Salem Alyafei; Abdul Jaleel (Innovations in Agriculture)
This study aimed to determine whether the application of different potassium salts (KCl, K2SO4, KNO3, KH2PO4) can alleviate the NaCl induced salinity in maize plants. NaCl stress decreased maize morphological parameters versus the control. NaCl combined with different type of potassium supplements were not significantly increased the root and stem length versus treatments with NaCl. However, a decrease in chlorophyll 'a', 'b', and total chlorophyll concentrations have been noted in the NaCl stressed plants when compared to control. The chlorophyll content rose with age in the leaves of control and treated plants. When compared to NaCl stressed plants, the chlorophyll content was higher in the NaCl with different types of potassium. Proline content increase in Maize plants under treatment with NaCl when compared to the control. To provide stress protection, several types of potassium are added along with NaCl to further reduce the proline concentration. Compared to the control, the phenol content of Maize plants treated with NaCl marginally increased. The phenol concentration was further raised by the addition of various potassium types along with NaCl, providing additional stress protection. The present study; therefore, suggests that exogenous potassium salts confers tolerance to salt stress to maize plants and have a significant role in partial alleviation of salinity stress especially in arid and semi-arid regions. Keywords: salinity, potassium salt, alleviation, biochemical, pigments